2011
DOI: 10.1126/science.1200320
|View full text |Cite
|
Sign up to set email alerts
|

Organic Aerosol Formation Downwind from the Deepwater Horizon Oil Spill

Abstract: A large fraction of atmospheric aerosols are derived from organic compounds with various volatilities. A National Oceanic and Atmospheric Administration (NOAA) WP-3D research aircraft made airborne measurements of the gaseous and aerosol composition of air over the Deepwater Horizon (DWH) oil spill in the Gulf of Mexico that occurred from April to August 2010. A narrow plume of hydrocarbons was observed downwind of DWH that is attributed to the evaporation of fresh oil on the sea surface. A much wider plume wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
162
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 19 publications
5
162
1
Order By: Relevance
“…It should also be noted that as the most volatile species in this study, HOA could be evaporated easily and thus have a larger potential to experience the "evaporation -oxidation in gas phase -condensation" process and then form SOA since previous studies showed that semi-volatile hydrocarbons from diesel exhaust (Robinson et al, 2007) and crude oil (de Gouw et al, 2011) can be easily oxidized in the gas phase to form less-volatile SOA. Huang et al (2012) also pointed out that HOA could be oxidized to SOA based on the analysis of their diurnal variations.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…It should also be noted that as the most volatile species in this study, HOA could be evaporated easily and thus have a larger potential to experience the "evaporation -oxidation in gas phase -condensation" process and then form SOA since previous studies showed that semi-volatile hydrocarbons from diesel exhaust (Robinson et al, 2007) and crude oil (de Gouw et al, 2011) can be easily oxidized in the gas phase to form less-volatile SOA. Huang et al (2012) also pointed out that HOA could be oxidized to SOA based on the analysis of their diurnal variations.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…For instance, gasoline vehicles emit 9-15 times or even 2 orders of magnitude higher secondary organic particulate matter than primary organic particle mass (Karjalainen et al, 2016;Nordin et al, 2013;Platt et al, 2013;Tkacik et al, 2014). Indeed, Bahreini et al (2012) found that secondary organic aerosol originating from gasoline engines forms the majority of the SOA in and downwind of large metropolitan areas. From diesel vehicles without a particle filter, the SOA mass formation potential is of the same magnitude as or lower than the primary particle mass emission Gordon et al, 2014b;.…”
Section: Introductionmentioning
confidence: 99%
“…The underestimation of SOA has been studied by many researchers. The existing models do not include certain precursors, such as semi-volatile organic compounds (SVOCs) and intermediate-volatility organic compounds (IVOCs) (Goldstein and Galbally, 2007;Robinson et al, 2007;de Gouw et al, 2011). Additionally, the existing precursors used in these models may lead to the underestimation of SOA (Tsimpidi et al, 2010), and the definitions of SOA and POA can vary (Cheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%